BAR-encapsulated nanoparticles for the inhibition and disruption of Porphyromonas gingivalis–Streptococcus gordonii biofilms - Mahmoud, Mohamed Y. (J Nanobiotechnology, 2018)
BACKGROUND: Porphyromonas gingivalis adherence to oral streptococci is a key point in the pathogenesis of periodontal diseases (Honda in Cell Host Microbe 10:423–425, 2011). Previous work in our groups has shown that a region of the streptococcal antigen denoted BAR (SspB Adherence Region) inhibits P. gingivalis/S. gordonii interaction and biofilm formation both in vitro and in a mouse model of periodontitis (Daep et al. in Infect Immun 74:5756–5762, 2006; Daep et al. in Infect immun 76:3273–3280, 2008; Daep et al. in Infect Immun 79:67–74, 2011). However, high localized concentration and prolonged exposure are needed for BAR to be an effective therapeutic in the oral cavity. METHODS: To address these challenges, we fabricated poly(lactic-co-glycolic acid) (PLGA) and methoxy-polyethylene glycol PLGA (mPEG-PLGA) nanoparticles (NPs) that encapsulate BAR peptide, and assessed the potency of BAR-encapsulated NPs to inhibit and disrupt in vitro two-species biofilms. In addition, the kinetics of BAR-encapsulated NPs were compared after different durations of exposure in a two-species biofilm model, against previously evaluated BAR-modified NPs and free BAR. RESULTS: BAR-encapsulated PLGA and mPEG-PLGA NPs potently inhibited biofilm formation (IC50 = 0.7 μM) and also disrupted established biofilms (IC50 = 1.3 μM) in a dose-dependent manner. In addition, BAR released during the first 2 h of administration potently inhibits biofilm formation, while a longer duration of 3 h is required to disrupt pre-existing biofilms. CONCLUSIONS: These results suggest that BAR-encapsulated NPs provide a potent platform to inhibit (prevent) and disrupt (treat) P. gingivalis/S. gordonii biofilms, relative to free BAR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12951-018-0396-4) contains supplementary material, which is available to authorized users.